Following the Epidemic Waves: Child and Youth Mental Health Assessments in Ontario Through Multiple Pandemic Waves - Stewart, Shannon L.; Vasudeva, Aadhiya S.; Van Dyke, Jocelyn N.; Poss, Jeffrey W. (Frontiers in Psychiatry, 2021)
Emerging studies across the globe are reporting an impact of COVID-19 and its related virus containment measures, such as school closures and social distancing, on the mental health presentations and service utilization of children and youth during the early stages of lockdowns in their respective countries. However, there is a need for longitudinal studies which examine the impact of COVID-19 on children and youth’s mental health and service utilization across multiple waves of the pandemic. The present study used data from 35,162 child and youth assessments across 53 participating mental health agencies in Ontario, Canada to assess mental health presentations and referral trends across the first two waves of the COVID-19 pandemic in the province. Data from each wave was compared to the equivalent period one year prior. While assessment volumes declined during both pandemic waves, child and youth assessments in low income neighborhoods declined more than those from high income neighborhoods during the second wave. There were also changes in mental health presentations noted in both waves. The proportion of depressive symptoms and risk of suicide and self-harm increased in both waves of the pandemic, whereas there were decreases in the prevalence of destructive/aggressive behavior, risk of injury to others, parents experiencing feelings of distress, anger, or depression, family feeling overwhelmed, and receiving child protective services in the last 90 days. Further, our results highlight that certain mental health concerns were exacerbated in the second wave. Notably, depressive symptoms and self-injurious attempts in the last month were more prevalent in the second wave of the pandemic when compared to the first. These findings highlight the multifaceted impact of multiple pandemic waves on children and youth’s mental health needs and underscore the need for future research into factors impacting children and youth’s access to mental health agencies during this time.